Evaluasi Implementasi Strategi Organisasi dalam Perspektif Model CIPP: Systematic Literature Review - Royan Roidi; I Dewa Ketut Kerta Widana; Dewi Puspaningtyas Faeni (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The implementation of organizational strategy is an important stage in strategic management that determines the success of achieving organizational goals. However, evaluation of strategy implementation still often focuses on the final outcome and does not use a comprehensive evaluation framework much. This study aims to analyze the development of research regarding the evaluation of the implementation of organizational strategies in the perspective of the Context, Input, Process, Product (CIPP) Model, identify the application of the CIPP dimension in the literature, and find research gaps and opportunities for future study development. The research uses the Systematic Literature Review (SLR) method with reference to the PRISMA 2020 guidelines. A literature search was conducted on the Scopus database and yielded 33 articles that met the inclusion criteria to be analyzed using narrative synthesis and thematic analysis. The results show that research based on the CIPP Model is still dominated by the fields of education, health, and training, while research on the implementation of organizational strategies focuses more on the success factors of the strategy. However, the dimensions of context, input, process, and product have a strong compatibility with the stages of implementing the organization's strategy. This study also identifies contextual, conceptual, and methodological gaps that show that there is still limited integration between the CIPP Model and the implementation of organizational strategies. These findings suggest that the CIPP Model has the potential to be a comprehensive evaluation framework for assessing the implementation of organizational strategies.